Pengaruh Gaya Kepemimpinan Terhadap Motivasi Kerja Karyawan Pada PT. Indonesia Penuh Rezeki Organizer (Indopor) Medan - Siahaan, Reza Valentino; Jumjuma, Jumjuma (Civiliza Publishing, 2025)
Leaders in a company have an important role in providing encouragement and motivation to their subordinates. Leaders basically have a certain leadership style to influence employees. Motivation provided by leaders within the company is one of the triggers for employees to increase their work productivity. If the motivation provided is lacking, employee productivity at work will also decrease. This research aims to determine the influence of leadership style on the work motivation of PT Indonesia Full Rezeki employees. The population of this study was 80 people and the sample used was 80 respondents (saturated). Data collection was carried out through questionnaires distributed in the form of Google forms via social media and through literature studies in the form of primary and secondary data. This research uses quantitative research methods with descriptive research types which include validity testing, reliability testing, classical assumption testing, hypothesis testing. The results of this research are that the directive leadership style variable has a positive and significant effect on work motivation, the supportive leadership style has no effect and is not significant on work motivation, the participative leadership style has no effect and is not significant and the achievement-oriented leadership style has no effect and is not significant, overall. simultaneously has a positive and significant effect. The research results from the coefficient of determination test (R^2) show that the leadership style variable explains the variation in work motivation by 65.4% and the remaining 34.6% is influenced by other variables not examined in this research